Success on Multiple Choice Examinations: A Model and Workshop Intervention - Bowering, Elizabeth R.; Wetmore, Ann A. (Canadian Journal of Counselling and Psychotherapy, 2007)
Our theoretical model first identifies the context in which students experience difficulties with complex multiple choice examinations (MCE) and then provides a structured approach to facilitate the development ofcritical thinking and metacognitive skills. Based on our model, we also designed a brief educational workshop, now in videotaped format. Workshop participants were taught that multiple choice (MC) questions assess lower and higher level critical thinking skills, and appropriate techniques for study and M C test-taking. To encourage the transfer of appropriate learning, participants then processed deeply, practiced, and mastered these messages through MC test simulations. O n anonymous questionnaires, participants reported increased knowledge concerning the process and content demands of complex MCE, as well as improved confidence and new behavioural skills.